Big data analytics as a management tool: an overview, trends and challenges - Mašić, Branislav; Dželetović, Milenko; Nešić, Sandra (Anali Ekonomskog fakulteta u Subotici, 2022)
Innovative digital technologies and ever-changing business environment have and will continue to transform businesses and industries around the world. This transformation will be even more evident in view of forthcoming technological breakthroughs, and advances in big data analytics, machine learning algorithms, cloud-computing solutions, artificial intelligence, internet of things, and the like. As we live in a data-driven world, technologies are altering work and work-related activities, and everyday activities and interactions. This paper provides a review of literature and recent researches on big data and big data analytics. Its aim is to explore the extent to which big data technologies are utilized in companies, and how the usage of big data technologies could better business performance and competitive advantage. Furthermore, this paper briefly presents main challenges that accompany the adoption of big data analytics in companies.